1994
DOI: 10.1159/000110363
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Dementia and Institutionalization in the Elderly: Prevalence Data from an Urban Area in Sweden

Abstract: This study investigated the severity of dementia in relation to disease type and sociodemographic variables. The dementia cases were detected with a two-phase study design in a population aged over 74 years in Stockholm. The prevalence of questionable, mild, moderate, and severe dementia was 1.0, 3.1, 5.5, and 2.3 per 100, respectively. Women aged over 84 had the highest prevalence of severe dementia. More severe cases and a higher institutionalization rate were present for vascular dementia than for Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…Our results confirmed the main contribution of dementia in institutionalization [1,8,40] . The very high burden of dementia within these institutions, previously reported between 66 and 73% [1,8] , has been estimated at 72% of institutionalized residents suffering from dementia in our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results confirmed the main contribution of dementia in institutionalization [1,8,40] . The very high burden of dementia within these institutions, previously reported between 66 and 73% [1,8] , has been estimated at 72% of institutionalized residents suffering from dementia in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The great majority of these cases were women. Even if severity of dementia cases is often evaluated [32] , few data have been published on the prevalence of dementia according to the severity of the disease [8][9][10][11] . However, as pointed out by Hy and Keller [11] , differences between studies in reported prevalence of dementia are lowered when including severity in the case definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement to include institutionalized persons in representative community samples has been subject to debate. Based on a metaanalysis covering prevalence studies from 1945 to 1985, Jorm et al [18] found no effect Corso et al [21] [22] Oslo/Norway (urban) 3.8 (13/334) -Fratiglioni et al [23] Stockholm/Schweden (urban) 7.8 (141/1,810) + Pi et al [24] Catalunya/Spain (semi-rural) 5.9 (26/440) + D'Alessandro et al [20] Sicily/Italy (rural) 10.6 (39/365) + + Included, -= not included. 1 Rate was derived by the author based on data given in the original paper; numbers in parentheses indicate the actual numerator and denominator figures.…”
Section: Discussionmentioning
confidence: 99%
“…The prospect of an increased burden on society in terms of health care has led to increased scientific interest in the different aspects of dementia in the last decades. Dementia appears to be more severe in patients with a presumed vascular cause [3,4]. Since vascular factors provide the best opportunities for prevention and intervention strategies, efforts have been made to distinguish a subgroup of patients with vascular dementia.…”
Section: Introductionmentioning
confidence: 99%